Allicin and Digestive System Cancers: From Chemical Structure to Its Therapeutic Opportunities - Sarvizadeh, Mahshad; Hasanpour, Omid; Naderi Ghale-Noie, Zari; Mollazadeh, Samaneh; Rezaei, Mohammad; Pourghadamyari, Hossein; Masoud Khooy, Mohammadjaber; Aschner, Michael; Khan, Haroon; Rezaei, Nima; Shojaie, Layla; Mirzaei, Hamed (Frontiers in Oncology, 2021)
Digestive system cancers tumors are one of the major causes of cancer-related fatalities; the vast majority of them are colorectal or gastric malignancies. Epidemiological evidence confirmed that allium-containing food, such as garlic, reduces the risk of developing malignancies. Among all compounds in garlic, allicin has been most researched, as it contains sulfur and produces many second degradation compounds, such as sulfur dioxide, diallylsulfide (DAS), diallyl trisulfide (DATS), and diallyl disulfide (DADS) in the presence of enzymatic reactions in gastric juice. These substances have shown anti-inflammatory, anti-diabetic, anti-hypertensive, antifungal, antiviral, antibacterial, and anticancer efficacy, including GI cancers, leukemia, and skin cancers. Herein, we summarize the therapeutic potential of allicin in the treatment of GI cancers.